Misy Sunshine Specialist Centre / Norazian Ahmad... [et al.] - Ahmad, Norazian; Mohd Radzi, Tengku Memy Nazhafifa; Hashim, Siti Hazarotul; Othman, Noor Hasniza Othman (2000)
Misy Sunshine Specialist Centre is a partnership business who runs services such as obstetrician, gynologist and outdoor patient. They were located at Kangar Perlis. Started their first run on 1 February 2002.